Biomass-derived mesopore-dominant hierarchical porous carbon enabling ultra-efficient lithium ion storage. (June 2020) - Qiu, Daping; Kang, Cuihua; Li, Min; Wei, Jinying; Hou, Zhiwei; Wang, Feng; Yang, Ru
Abstract: Amorphous hierarchical porous carbon with capacity and energy storage kinetics superior to graphite anodes is considered to be an ideal alternative to conventional lithium-ion battery anodes. Herein, a versatile plant-derived mesopore-dominant hierarchical porous carbon (KHPC) has been successfully fabricated using KClO4 as a synchronous activator and template through a facile one-step synthesis strategy. Serving as the anode material, the obtained KHPC exhibits ultra-efficient lithium ion storage performance, including high reversible specific capacity (1064 mA h g −1 at 0.1 A g −1 ), excellent rate capability (250 mA h g −1 even at 10 A g −1 ) and long lifespan (93% retention after 2000 cycles). A lithium-ion batteries full-cell is constructed, which demonstrates high energy density (230 Wh kg −1 at 335 W kg −1 ) and long-term cycling stability. Furthermore, the constructed lithium-ion hybrid capacitors deliver extraordinary energy/power density (169 Wh kg −1 and 97 kW kg −1 ), as well as ultra-long durability (77.7% retention after 5000 cycles). This work provides a new alternative route for large-scale synthesis of high-performance plant-derived carbon for electrochemical energy storage. Graphical abstract: A versatile plant-derived mesopore-dominant hierarchical porous carbon (KHPC) has been successfully fabricated using KClO4 as a synchronous activator and template through a facile one-step synthesis strategy, then it was successfully applied to construct lithium-ion batteries and lithium-ion hybrid capacitors. Image 1